Study of immune status dynamics in rats with induced benign prostatic hyperplasia - Lul’ko, S.; Savytskyi, I.; Ostapets, M. (Journal of Education, Health and Sport, 2024)
The article presents the results of a study on pro- and anti-inflammatory cytokines in rats with experimentally induced benign prostatic hyperplasia. It was found that the levels of tumor necrosis factor-α, interleukin-8, and interleukin-6 – pro-inflammatory cytokines – increased sharply, while the levels of anti-inflammatory cytokines, on the contrary, decreased. In addition, there was a significant increase in tissue growth factor-β, which may indicate progressive fibrotic proliferation in the prostate gland. The obtained data on the dynamics of plasma and prostatic levels of cytokines interleukin-8 and interleukin-10 suggest that despite changes in their concentrations, the most pronounced imbalance occurs at the organ level (in prostate homogenate). This is characterized by excessive secretion of the pro-inflammatory cytokine interleukin-8 against the background of a relative deficiency of the anti-inflammatory cytokine interleukin-10, which supports the hypothesis about the important role of cytokine imbalance in the activation and persistence of chronic aseptic inflammation in the prostate.